2018
DOI: 10.2478/sab-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Producer Groups – Increasing Producer’s Value Aded?

Abstract: Cooperation between entities can be the basis for improved competitiveness. The Czech Republic and the Slovak Republic were able to draw on EU funds to support the formation of producer groups. Main objective was to investigate whether the funds have led to an increase of value added of products placed on the market. In the Czech Republic and the Slovak Republic during the reporting period the sum of 44 million EUR was provided to support the establishment of marketing organizations, 305 producer groups were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many of the supported units are no longer active. In these countries, only over twenty organisations still operate, but they do not have a significant impact on the increase in the added value of the agricultural sector (Kotyza et al, 2018). In Slovakia, we also note that reducing the number of groups by 40% resulted in a decrease in the number of associated members by 49%.…”
Section: Resultsmentioning
confidence: 69%
“…Many of the supported units are no longer active. In these countries, only over twenty organisations still operate, but they do not have a significant impact on the increase in the added value of the agricultural sector (Kotyza et al, 2018). In Slovakia, we also note that reducing the number of groups by 40% resulted in a decrease in the number of associated members by 49%.…”
Section: Resultsmentioning
confidence: 69%
“…In analyzing the effect of the RDP support on the establishment of APOs in the Czech Republic and Slovakia, Kotyza et al (2018) found differences in the design and implementation of the APO support policies. They assess the Slovak policy as more successful.…”
Section: Literature Reviewmentioning
confidence: 99%